Performance analysis of SWOT suite toolkit on Inter-domain and Intra-domain Web of Things - Anuar, Nur Ameera; Wahid, Norfaradilla (Penerbit UTHM, 2017)
The Web of Things (WoT) is a term used to describe approaches, software architectural styles and programming patterns that allow real-world objects to be part of the World Wide Web [1]. Similarly to what the Web (Application Layer) is to the Internet (Network Layer), the Web of Things provides an Application Layer that simplifies the creation of Internet of Things applications [2].